Development of cognitive vehicle assistance and driver safety control management - Ankamma rao, B; Harika Devi, M; Veni Kommuri, Krishna (International Journal of Engineering and Technology, 2018)
In this paper we present new approach for automobiles safety driving system involving the multiple sensor monitoring an area around vehicle and conveying alert the driver.Â There is some distance between two vehicles if apply break we can lose the control our vehicle. The proposed system works like that it has the four Ultrasonic sensors are fixed four sides of car they will detect the cars and obstacles within in the monitored area based on how much distance they are near to car and alert the driver via leds.an alcohol sensor fixed in the steering if he driver drink alcohol it will detect and switch off the vehicle ignition. The IR sensor monitors the eye blinks the driver. If the driver sleeps it makes ring the buzzer.Â